Empowerment of Jambi Malay Tribe Women through Batik Staple Fabric Processing to Improve Economic Welfare - Muazza, Muazza; Mayasari, Mayasari; Muslim, Fachruddiansyah; Syuhada, Siti; Refnida, Refnida (LP2M INSURI Ponorogo, 2025)
creatively processing Jambi batik patchwork into home décor products and improves economic welfare. The initiative provides women with essential skills to produce valuable home décor items such as decorative cushions, tablecloths, and wall art from batik patchwork, a material traditionally considered textile waste. The program focuses on processing batik scraps into home décor products for wall hangings. By focusing on design, production, and digital marketing skills, the program fosters economic independence and strengthens the role of women in the local economy. The purpose of this service activity is to provide training and skills to Jambi Malay tribe women to produce home decor from batik scraps and transform batik scraps into home decor products with high added value to increase product competitiveness, develop and promote local product culture, and increase economic income. The results of the service showed practical skills, increased income, self-confidence, and social status of the participants. This sustainable approach promotes environmental conservation and supports local economic resilience, proving the long-term positive impact of empowering women in the creative industry on community welfare.